2019
DOI: 10.1177/1535370219834639
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to 50 Hz electromagnetic fields enhances hair follicle regrowth in C57BL/6 mice

Abstract: Many studies have suggested that electromagnetic field activity affects the cellular activity of many types of cells involved in forming hair follicles. However, the bio-effects of electromagnetic fields on hair follicle growth have not been fully elucidated. This present study was designed to determine whether 50 Hz electromagnetic fields increased hair follicle regrowth. In this experiment, C57BL/6 mice were used to present the model of depilation-induced hair follicle cycling, and then those mice were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…KGF gene, also known as FGF7 , belongs to the FGFs gene family and is an epithelial-specific growth factor that can specifically stimulate the proliferation of epithelial cells such as keratinocytes [ 20 ]. Li [ 21 ] found that the KGF gene exists in the inner root sheath of mouse feather follicles and may play a regulatory role. Since the stromal cells of the inner root sheath produce the feather shaft and KGF receptors are present on the stromal cells, it is speculated that KGF may promote feather growth.…”
Section: Discussionmentioning
confidence: 99%
“…KGF gene, also known as FGF7 , belongs to the FGFs gene family and is an epithelial-specific growth factor that can specifically stimulate the proliferation of epithelial cells such as keratinocytes [ 20 ]. Li [ 21 ] found that the KGF gene exists in the inner root sheath of mouse feather follicles and may play a regulatory role. Since the stromal cells of the inner root sheath produce the feather shaft and KGF receptors are present on the stromal cells, it is speculated that KGF may promote feather growth.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐frequency electromagnetic fields facilitate the generation of bio‐engineered hair follicles 26 and increase the expression of anagen‐related molecules in human dermal papilla cells 8 . Exposure to electromagnetic fields enhances hair club formation via increased proliferation of epidermal stem cells from the bulge region and facilitates the development of a new lower follicle 9 . Motion‐activated and wearable electric stimulation devices effectively accelerate hair growth and promote hair follicle formation 27 …”
Section: Discussionmentioning
confidence: 99%
“…It enhances the activation and proliferation of dermal papilla cells in the human hair follicle 8 . Xinping Li et al found that treatment with 50 Hz electromagnetic field leads to an increase in hair length in hair follicle cycling models 9 . Clinically, the use of electromagnetic pulses to treat AGA was corroborated by Maddin, 10,11 who showed that PEMF stimulated hair growth.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, lower frequencies, such as ELFs, may promote hair growth, thus emphasizing the importance of dose, frequency, and strength on the impact of electromagnetic radiation on the body. 28 A meta-analysis was performed of the in vitro effects of RF-EM on human and animal cells. Of the 746 human cell experiments, 45.3% of studies demonstrated a significant effect of RF energy on cells, whereas 54.7% did not (p 5 .001).…”
Section: Radiofrequency Electromagnetic Radiation Affects Our Hair Cellsmentioning
confidence: 99%